Perception of circular economy approach in agricultural cooperatives of Argentina - Rotolo, Gloria Claudia; Vasillo, Chiara; Rodriguez Aranza, Ailén; Magnano, Luciana; Milo Vaccaro, Marcelo; Civit, Bárbara María; Arena, Alejandro Pablo (Universidade Paulista - Università degli Studi di Ferrara, 2022)
Circular Economy approach is imposing as a framework for changing the current environmental-socio-economic constrains as well as building a new paradigm where citizens in all their society roles has a key participation on its principles such as to design out waste and pollution, to keep products and material in use and to regenerate natural systems. However, implementation in Argentina is very slow and only applied at some companies’ level, as some agricultural cooperatives, or at urban residues recycling at certain cities. The objective of this paper is to explore the awareness, current state and expectations of the transition towards a circular economy approach within agricultural cooperatives based on opinion and perception/awareness consultation. This paper communicate the results obtained from a wider Project, which analyzed others activity sectors of Argentina. An anonymous questionnaire was designed and implemented in order to obtain the objective, and it was structured into three sections: i) demographic characterization, ii) general awareness about transition towards circular economy (concept, current state, features, advantages, drivers, barriers and governance) and iii) specific issues within the cooperative sector. Results explore the perception/awareness about the transition towards applications, barriers, governance of circular economic mechanisms providing an interpretative framework of current state, expectations and possibilities of action to both researchers and policy makers.